2013
DOI: 10.1016/j.biopsych.2012.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Response Inhibition in Bipolar Disorder: A Functional Magnetic Resonance Imaging Study of Trait- and State-Related Abnormalities

Abstract: Background Impaired response inhibition and poor impulse control are hallmarks of the manic phase of bipolar disorder but are also present during depressive and, to a lesser degree, euthymic periods. The neural mechanisms underlying these impairments are poorly understood, including how mechanisms are related to bipolar trait or state effects. Methods One-hundred four unmedicated participants with bipolar mania (BM) (n = 30), bipolar depression (BD) (n = 30), bipolar euthymia (BE) (n = 14), and healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 51 publications
0
45
0
Order By: Relevance
“…In a study of response inhibition using the stop signal task, significantly less activation in the left IFG (BA 47) and the nucleus accumbens was reported in a medicated sample of adults and youths with bipolar disorder across mood states and combined subtypes I and II compared with healthy controls (Weathers et al, 2012). To our knowledge, there are only two other studies of response inhibition in adult BP depression (Hummer et al, 2013;Radaelli et al, 2013) and both used a Go/NoGo task with emotional and nonemotional stimuli. During the nonemotional contrast, one study reported greater activity in the left putamen in BP manic and euthymic groups compared with the control group (Hummer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study of response inhibition using the stop signal task, significantly less activation in the left IFG (BA 47) and the nucleus accumbens was reported in a medicated sample of adults and youths with bipolar disorder across mood states and combined subtypes I and II compared with healthy controls (Weathers et al, 2012). To our knowledge, there are only two other studies of response inhibition in adult BP depression (Hummer et al, 2013;Radaelli et al, 2013) and both used a Go/NoGo task with emotional and nonemotional stimuli. During the nonemotional contrast, one study reported greater activity in the left putamen in BP manic and euthymic groups compared with the control group (Hummer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to fill a significant gap in the understanding of response inhibition in adults with bipolar depression, as there is only one other such study in the literature (Hummer et al, 2013). Understanding BP across mood states is essential for identifying neural patterns that may serve as potential trait markers for this disorder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies reported an insular dysfunction in Schizophrenia, Bipolar Disorder, and "at-risk subjects", during both tasks [110][111][112][113][114][115] and resting state [116][117][118][119] , thus suggesting a key role of this region in vulnerability for psychosis, regardless of the affective or non-affective diagnostic distinction.…”
Section: Ref Participants Task and Behavioral Results Fmri Methods Amentioning
confidence: 99%